Adapting to Climate Change: Food Security Policy Strategies in Makassar City, Indonesia - Risnawati, Risnawati; Salam, Eka Fitra Ramadani; M, Nursafitra (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
Food is one of the crucial elements in supporting the sustainability of life and is a fundamental component in supporting Sustainable Development in Indonesia. The current Food Condition of Makassar City still faces several obstacles in its implementation. Several factors include the unfulfilled diversity of existing food, insufficient public understanding of food diversification, consumption and diversity, suboptimal fulfilment of family food and nutritional needs, food availability which is still predominantly plant-based, and suboptimal public health. This study aims to analyze how the Food Security Policy Strategy is implemented in addressing Climate Change in Makassar City. The research method employed in this study is a qualitative approach with data collection techniques through in-depth interviews and document reviews. The results of the study were processed through the stages of data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the policy strategies implemented in addressing climate change in Makassar City are: 1) The Tourism Corridor Program (Longwis) utilizing the Urban Farming method, 2) Implementing climate change adaptation policies through Accelerating the flow of climate information in Makassar City, 3) Makassar City Food Diversification Policy with the development of superior commodities that are appropriate for the Makassar City area. The results of this study are expected to serve as a reference for the government, particularly the Makassar City government and other regions in Indonesia, to develop a Food Security Policy Strategy in Facing Climate Change that can occur at any time, ensuring that sufficient food is met, both in terms of quantity and quality, so that people live healthily and productively in a sustainable manner.